Sensory Attribute Profiling and Consumer Preferences of Payus Fish (Elops Hawaiensis) Crackers Produced by Small And Medium Enterprises in Surabaya City - Chika Safira Riyananda; Ulya Sarofa; Yunita Satya Pratiwi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Payus fish crackers (Elops hawaiensis) are a popular fishery-based snack in Surabaya, with sensory characteristics varying among producers due to differences in formulation and processing. This study aimed to identify the sensory profile of payus fish crackers, determine consumer preferences, and analyze the relationship between sensory attributes and consumer liking of products from small and medium enterprises (SMEs) in Surabaya. Sensory evaluation was conducted using the Rate-All-That-Apply (RATA) method with consumer panelists. Focus Group Discussion (FGD) identified 17 sensory attributes covering color, aroma, texture, taste, mouthfeel, and aftertaste. RATA analysis showed significant differences in sensory intensity among the five samples, influenced by ingredient composition and processing methods. Preference mapping indicated that sample 928 was the most preferred, characterized by distinct fish taste and aroma, crunchy texture, and fish aftertaste. Sample 501 was also highly preferred due to its fried aroma, yellow color, salty and sweet taste, grainy mouthfeel, and crispy texture. In contrast, sample 836 was less preferred because of its oily mouthfeel and greasy aftertaste, while sample 342 was less favored due to its dominant white color. Contribution to Sustainable Development Goals (SDGs):SDG 1: No Poverty SDG 8: Decent Work and Economic GrowthSDG 2: Zero Hunger